Legal Responsibility Of Land Deed Officials (PPAT) In The Implementation Of Government Regulation In Lieu Law (Perpu) Number 56 Of 1960 Concerning The Determination Of Agricultural Land Area - Noor, Aslan; Salsabilla, Ainul Mardiyah; Meutia, Irviana; Subrata, Nabila Djuliana Suria; Saraswati, Nabila Trina Saumah (UNIVERSITAS PAKUAN, 2025)
Land reform policy is a strategic step towards creating equitable land ownership and eliminating agrarian inequality. In its implementation, Land Deed Officials (PPAT) play an important role because the deeds they draw up form the legal basis for the transfer or encumbrance of land rights. This study aims to analyse the role of PPAT, the form of their legal responsibility, and the obstacles in the implementation of land reform. This study uses a normative juridical method with a legislative, conceptual, and case approach. The results of the study show that PPATs have administrative, civil, and criminal legal responsibilities, but practices in the field face various obstacles, such as weak supervision, limited land data, and potential violations of the code of ethics. Therefore, strengthening regulations, digitising land administration, and improving the integrity of PPATs are necessary to achieve the objectives of land reform.